G46 Improving the hospital experience for young people (YP) with autism. (24th May 2017) - Datt, C; Travers, M; Odell, C
Abstract : Introduction: Young People (YP)'s, with autism are often labelled as difficult or challenging in hospital. Staff in acute health settings are often ill-equipped to communicate with and support these YP's, thus they generally have poorer experience of care in Acute Paediatric Services. Aim: We engaged 3 young people with Autism to do a joint review of our paediatric services and to review the engagement of our staff, with Autistic YP's Methods: These YP's, who had used local health services, spent a morning reviewing the inpatient and outpatient clinical areas. They interviewed the reception staff, nursing staff and play specialists. The YP's used a survey, they had designed and scored the areas and staff on a numerical scale. Results: The signage in the ward area was described as inadequate, however the reception area had better signage and the staff were friendly and helpful. The waiting area in our outpatient department was easy to find, clean and tidy, however the noise and lighting proved distracting. There were not enough fidget toys in the clinical procedures areas. Ward and outpatient staff scored well on their understanding of autism, but it was suggested that additional training would empower staff. The waiting area in our outpatient department was easy to find and clean and tidy, however the noise and lighting proved distracting. All staff were receptive to comments during the inspection and treated the YP's with respect. Conclusion: The YP's made several recommendations, in terms of the environment and patient experience. All staff will now receive autism awareness training; we have set up an alert on our patient information system. Patients with autism will can be offered ear defenders, if noise sensitive patients and fidget toys if requested. We can now offer a 'quiet' room to autistic young people if necessary. New signs have been put up throughout the requested sites to meet the needs of our autistic young people. There is an Action Plan in progress, aiming to meet all changes recommended. We will invite the YC's back to re-audit once all the changes are complete.